A Comparative Study of Korean and Chinese Adventure Movies Taking "Himalaya" and "The Climbers" as an Example - Ge, Houyu (Journal of International Culture & Arts, 2021)
Today, adventure film has become the measure of film level for its popularity and mainstream status in the film market. It also tests film creators’ understanding of multiculturalism and filming technology. Adventure movies can not only bring a strong sense of participation to the audience, but also help you experience foreign culture and scenery which you never see before, and arouse the audience’s reflection on their living environment. Adventure movies always shock the audience with dangerous environment, tense storylines and ubiquitous death. After the nightmare story disappears, it brings psychological peace and inspirational theme to the audience. This paper focuses on the two adventure films of Himalaya (Korean Film) and Climber (Chinese Film). Both adventure films reflect the story of the Himalayan mountaineering from different angles based on real incidents, showing the solemn and beautiful scenery of the Himalaya Mountain, and conveying the plight and hardships of the mountaineering to the audience. The two films both depict the awe of the Himalayas and the noble spirit of climbers who are brave enough to climb. However, due to the cultural differences between the two countries, there are great differences in the film presentation art in the two films by showing different artistic characteristics. This paper analyzes and compares the two films, and summarizes the similarities and differences in the theme, narrative strategy, image design and so on in different cultural backgrounds. We hope to promote the exchange of film culture between the two countries and expand the deep cooperation in the field of adventure film through this paper. KCI Citation Count: 1